Function and Evolution of Nuclear Receptors in Environmental-Dependent Postembryonic Development - Taubenheim, Jan; Kortmann, Constantin; Fraune, Sebastian (Frontiers in Cell and Developmental Biology, 2021)
Nuclear receptors (NRs) fulfill key roles in the coordination of postembryonal developmental transitions in animal species. They control the metamorphosis and sexual maturation in virtually all animals and by that the two main environmental dependent developmental decision points. Sexual maturation and metamorphosis are controlled by steroid receptors and thyroid receptors, respectively in vertebrates, while both processes are orchestrated by the ecdysone receptor in insects. The regulation of these processes depends on environmental factors like nutrition, temperature or photoperiods and by that NRs form evolutionary conserved mediators of phenotypic plasticity. While the mechanism of action for metamorphosis and sexual maturation are well studied in model organisms, the evolution of these systems is not entirely understood and requires further investigation. We here review the current knowledge of nuclear receptor involvement in metamorphosis and sexual maturation across the animal tree of life with special attention to environmental integration and evolution of the signaling mechanism. Further, we compare commonalities and differences of the different signaling systems. Finally, we identify key gaps in our knowledge of nuclear receptor evolution, which, if sufficiently investigated, would lead to an importantly improved understanding of the evolution of complex signaling systems, the evolution of life history decision points, and, ultimately, speciation events in the metazoan kingdom.